Hubungan Obesitas, Usia, dan Riwayat Kanker Payudara dalam Keluarga dengan Kejadian Kanker Payudara di RSUD Provinsi NTB - Khairiyah, Dinur; Suanjaya, Made Agus; Setyobudi, Irwan; Santosa, Hilda (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine whether there is a relationship between obesity, age, and family history of breast cancer with the incidence of breast cancer at the NTB Provincial Hospital. This study used an analytic cross-sectional research design. The sampling technique employed purposive sampling, with 286 samples meeting the inclusion criteria analyzed using the Pearson Chi-Square test. Based on the study results, among 286 breast cancer respondents, the number of stage I breast cancer patients was 49 respondents (17,1%), stage II was 119 respondents (41,6%), stage III was 95 respondents (33,2%), and stage IV was 23 respondents (8%). This study found a significant relationship between obesity and the incidence of breast cancer with a p-value of 0,043. However, there was no significant relationship between age and the incidence of breast cancer (p-value 0,123), nor between a family history of breast cancer and the incidence of breast cancer (p-value 0,166).